"Laughing moments": the complex negotiation of laughing acts among students and teachers in an English as a second language classroom. Issue 1 (2nd January 2022) - Matsumoto, Yumi; Lee, Jay Jo; Kim, Eunhee
ABSTRACT: Using multimodal conversation analysis, this study closely examines moments when an instructor's embodied explanations elicit laughter from his students – which we refer to as laughing moments – in an English as a second language classroom. Such laughing moments can exhibit students' attention to the teacher's explanation and also illuminate learner agency in deciding what is laughable and/or humorous. In particular, the negotiated nature of laughter and humour – how students orient to and select what is laughable and/or humorous – has been under-researched. Based on the findings, we discuss implications of a multimodal orientation for second language (L2) classroom research on laughter and humour, and implications for L2 teachers concerning negotiating laughter and humour with students.